PENYELESAIAN TANAH KORBAN TSUNAMI YANG TIDAK ADA DAN/ATAU TIDAK DIKETAHUI AHLI WARISNYA - Taqwaddin Taqwaddin; Sulaiman Tripa; Insa Ansari; Teuku Muttaqin Mansur (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
Post-tsunami disaster in Aceh, legal issues on land are regulated by the Government Regulation in Lieu of Law Number 2 of 2007, which regulates among others on land that does not exist and/or unknown its owners and their heirs. The land is being taken care as a religious treasure by Baitul Mal with an order the Syar'iyah Court. This study applies juridical normative and sociological normative methods. From the field research it was found that the Government did not have data of lands with unknown owners and their heirs. It was known from decision of the Syar'iyah Court of Banda Aceh which revealed that the fact was originated from the construction of the drainage where the land procurement committee did not know where to hand over the land acquisition fund.Key words: tsunami, land, Aceh